Electron spin resonance of molecular magnets for quantum information processing - Kaminski, D (2015)
Quantum information processors have been shown theoretically to outperform their classical counterparts at certain tasks. They comprise two level systems, which can exist in an arbitrary superposition of states: qubits. A strong candidate qubit is the molecular nanomagnet (MNM). In this thesis, electron spin resonance is used to explore the potential of Cr7M based MNMs as elements of a quantum information processor. We explore the possibility and effect of replacing H atoms with D or a halogen atom in a S = 1/2 Cr7Ni ring. Decoherence mechanisms in the resulting compounds are found to be dominated by structural effects. We conclude that halogenation does not seem to be a productive strategy for extension of coherence times in Cr7Ni based compounds. We examine an asymmetric dimer, in which a Cr7Ni ring is linked to a highly coherent nitrogen atom within a carbon cage. Measurement of phase memory time across a range of temperatures for the N spin, provides insight into the ring's spin dynamics. At high temperature, fluctuations on the ring are so rapid that the N spin appears magnetically disconnected; as they slow, we see a sharp rise in the decoherence rate of the N spin. At the lowest temperatures, a recovery of the decoherence rate reflects the onset of the ring’s coherent ground state. A group of symmetric Cr7Ni-Cr7Ni dimers is investigated. Through use of double electron-electron resonance, the strength of the ring-ring dipolar interaction, governing the two qubit gate time, is estimated for each. It is found that many exhibit the hierarchy of timescales required for implementation of a two qubit gate: a short single qubit manipulation time, intermediate two-qubit gate time and long phase coherence time. A possible scheme for the future implementation of a CNOT gate is presented. The final study explores rings of spin, S > 1/2. We present the first ever coherent measurements on a dilute oriented ensemble of the S = 3/2 rings, Cr7Zn, performing nutations at various powers. In addition, we investigate the anisotropic Mn2+ (s = 5/2, I = 5/2) defect in ZnO. We develop the 'echo kill' method for identification of a three level subsystem whose transition frequencies both fall within the cavity bandwidth. Such a subsystem is then used to perform indirectly detected nutations between the upper two levels over a range of applied powers. Finally, a method for initialisation of the subsystem into a pseudopure state is presented and shown to enhance nutation amplitude.